2019
DOI: 10.1038/s41416-019-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Apelin and apelin receptor expression in renal cell carcinoma

Abstract: BACKGROUND: The APLNR (apelin receptor) has been shown to be an essential gene for cancer immunotherapy, with deficiency in APLNR leading to immunotherapy failure. The aim of this study is to investigate the expression of APLN (apelin) and APLNR in patients with renal cell carcinoma (RCC), and its association with clinicopathological parameters and survival. METHODS: Three well-characterised patient cohorts with RCC were used: Study cohort 1 (clear-cell RCC; APLN/APLNR mRNA expression; n = 166); TCGA validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…According to our results and a previous study, the interactions among CXCRs, CXCL1, and CCL5 may mediate the regulatory T cells' participation in ccRCC progression (Wang et al, 2019). Recently, APLN receptor (APLNR) was considered to be an essential gene for tumor immunotherapy, which can modulate the function of CD8+T cells, but the immunological effects of the APLN/APLNR axis in ccRCC remain unknown (Tolkach et al, 2019). On the basis of previous research and our current results, we speculate that CXCRs may interact with APLN/APLNR axis to regulate the immune state of the tumor microenvironment in ccRCC.…”
Section: Discussionsupporting
confidence: 54%
“…According to our results and a previous study, the interactions among CXCRs, CXCL1, and CCL5 may mediate the regulatory T cells' participation in ccRCC progression (Wang et al, 2019). Recently, APLN receptor (APLNR) was considered to be an essential gene for tumor immunotherapy, which can modulate the function of CD8+T cells, but the immunological effects of the APLN/APLNR axis in ccRCC remain unknown (Tolkach et al, 2019). On the basis of previous research and our current results, we speculate that CXCRs may interact with APLN/APLNR axis to regulate the immune state of the tumor microenvironment in ccRCC.…”
Section: Discussionsupporting
confidence: 54%
“…PTGER3, CDCT2 and APLN have positive effects on overall survival time, but CXCL5 and GRM4 have negative effects on it. Research demonstrated that APLN could interact with APLN receptor, which is a G-protein-coupled receptor, which may influence the aggressive of ccRCC and the effect of immune therapy 56 . And C-X-C chemokine receptor 4 (CXCR4) is the major chemokine receptor in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In another glioma study targeting APLNR with a competitive antagonist reduced tumor growth in mice [190]. In a renal cell carcinoma study, APLNR expression in a subset of patients was found to be negatively correlated with tumor PD-L1 expression [177]. This also indicates a role of APLN/APLNR signaling in the regulation of immunological processes, which needs to be further investigated.…”
Section: Apelin/aplnr Pathwaymentioning
confidence: 99%
“…The APLN/APLNR pathway is upregulated in malignant cells in many tumor types [174,176,177], as well as in tumor endothelial cells [178], and elevated Apelin levels are associated with disease progression and poor clinical outcome [176,[179][180][181]. Apelin expression in tumors is regulated by hypoxia [181] and is suggested to promote tumor growth in several ways.…”
Section: Apelin/aplnr Pathwaymentioning
confidence: 99%